2021
DOI: 10.1111/tid.13660
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of malaria from donors to solid organ transplant recipients: A case report and literature review

Abstract: Malaria is a febrile and potentially fatal infection. It is typically transmitted to humans through the bite of Anopheles mosquitoes and less frequently can be contracted through blood transfusions, sharing contaminated needles and syringes, mother-tochild transmission, or after solid organ transplantation. Posttransplant malaria has rarely been reported in the literature, even in endemic areas. We report the cases of three solid organ recipients in which Plasmodium vivax infection was documented during postsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…If this donor had presented in Florida, there would be a concern for Malaria, given the cases of local transmission identified in 2023. 7,8 Without the demographic information provided, the differential broadens further to include other parasitic infections and viral encephalitis such as West Nile Virus, 9 many of which have high penetrance to organ recipients. This case highlights the potential for transmissibility of infection within a newly transplanted organ.…”
Section: Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…If this donor had presented in Florida, there would be a concern for Malaria, given the cases of local transmission identified in 2023. 7,8 Without the demographic information provided, the differential broadens further to include other parasitic infections and viral encephalitis such as West Nile Virus, 9 many of which have high penetrance to organ recipients. This case highlights the potential for transmissibility of infection within a newly transplanted organ.…”
Section: Casesmentioning
confidence: 99%
“…Keeping up to date on outbreaks is important given the concern for transmission of diseases from donor to recipients. If this donor had presented in Florida, there would be a concern for Malaria, given the cases of local transmission identified in 2023 7,8 . Without the demographic information provided, the differential broadens further to include other parasitic infections and viral encephalitis such as West Nile Virus, 9 many of which have high penetrance to organ recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Rarely, malaria transmission via organ transplantation has been reported. In a recent case series, authors reported P. vivax infections in three patients who received a liver, kidney, or a heart transplant from a single donor who was later found to have had malaria prior to his death [15 ▪ ]. Their review suggested that the laboratory and clinical features of P. vivax infection in transplant recipients could be severe and included thrombocytopenia, hemolytic anemia, fever and graft dysfunction due to hemodynamic changes.…”
Section: New Insights Into Pathogenesismentioning
confidence: 99%
“…4 However, it can also be transmitted by blood transfusion, transplacental, organ transplantation, and through the use of improper syringes. 5 Regarding transfusion-transmitted malaria (TTM), in Brazil, a single case was reported in São Paulo in 2011. 6 Nevertheless, there is a lack of data about the prevalence of asymptomatic infected blood donors in such urban areas across Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…The parasite is spread by the bite of female Anopheles mosquitoes 4 . However, it can also be transmitted by blood transfusion, transplacental, organ transplantation, and through the use of improper syringes 5 …”
Section: Introductionmentioning
confidence: 99%